Cartography of care production in the Family Health Strategy (Research, Society and Development, 2021)
The objective was to map the elements of care production present in the Family Health Strategy. It was a study carried out in a Family Health Unit, with a population of 7,881 families, in Fortaleza-CE, Brazil. Research population comprised twelve health workers and four service users, who shared data production workshops. Cartography demonstrated emphasis in multiplicities due to the polyphony expressed in communicational relations and the polysemy in the service routine. It was observed the existence of spaces, whose care production is crystallized, with a discourse of shortage, which can immobilize subjects (workers and users). Escape lines were produced and provided loopholes to indicate desired and possible paths. It is understood that through the awakening of the vibrating body with the potential to affect meetings the production of new concepts and, consequently, care practices committed to health production will occur.